WORK ENGAGEMENT AMONG HAJJ PERSONNEL: THE ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT IN THE PANITIA PENYELENGGARA IBADAH HAJI (PPIH) - Novia Sarmila Ramadhan; Reny Yuniasanti; Hazalizah binti Hamzah (Dinamika Psikologis: Jurnal Ilmiah Psikologis, 2026)
This study aims to examine the relationship between perceived organizational support and work engagement among members of the Hajj Organizing Committee (Panitia Penyelenggara Ibadah Haji). A quantitative research design was employed using a purposive sampling technique. The inclusion criteria consisted of active committee members who had a minimum tenure of three months. Data were collected using the Utrecht Work Engagement Scale and the Survey of Perceived Organizational Support. The study involved 79 participants, and data analysis was conducted using SPSS version 25. The relationship between variables was analyzed using the Pearson Product–Moment correlation technique. The results indicated a significant positive relationship between perceived organizational support and work engagement (r = 0.963, p < .05). These findings highlight the importance of organizational support in fostering employee engagement within public service organizations, particularly in the context of Hajj administration. Keywords: Panitia Penyelenggara Ibadah Haji, Perceived organizational support, Work Engagement